2007
DOI: 10.1055/s-2007-993744
|View full text |Cite
|
Sign up to set email alerts
|

Mycological and Electron Microscopic Study of Solanum chrysotrichum Saponin SC-2 Antifungal Activity on Candida Species of Medical Significance

Abstract: Solanum chrysotrichum is utilized in traditional Mexican medicine for the treatment of mycotic skin infections. Several microbiological studies have provided evidence of its antifungal activity against dermatophytes and yeasts. S. chrysotrichum saponins have been identified as a group of compounds with antifungal activity and saponin SC-2 has demonstrated to be the most active. Previous clinical studies have shown the therapeutic effectiveness of S. chrysotrichum-derived saponin-standardized herbal products in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…It was shown to have a similar clinical effectiveness to that of ketoconazole, but obtained a smaller percentage of mycological effectiveness and 100% tolerability (Herrera-Arellano et al 2013 ) . An additional study found the Saponin SC to be effective against candida non-albicans species, or fluconazole and ketoconazole resistant strains of yeast (Herrera-Arellano et al 2007 …”
Section: Solanum Chrysotrichummentioning
confidence: 99%
“…It was shown to have a similar clinical effectiveness to that of ketoconazole, but obtained a smaller percentage of mycological effectiveness and 100% tolerability (Herrera-Arellano et al 2013 ) . An additional study found the Saponin SC to be effective against candida non-albicans species, or fluconazole and ketoconazole resistant strains of yeast (Herrera-Arellano et al 2007 …”
Section: Solanum Chrysotrichummentioning
confidence: 99%
“…The rigid planar structure of delphinidin-3-O-sambubioside and cyanidin-3-O-sambubioside and the presence of ortho-dihydroxylation on the aromatic ring probably contributed to the inhibition of ACE [12] . Another clinical trial, conducted on 193 patients with hypertension stages I and II, carried out by Herrera-Arellano et al also confirmed the inhibition of ACE activity through using watery infusions of HS [42] . The trial showed that HS calyxes could significantly reduce plasma ACE activity.…”
Section: Inhibition Of Ace Activitymentioning
confidence: 76%
“…Daily consumption of 500 mg of HS calyx powder could reduce systolic blood pressures and serum triglycerides in metabolic syndrome patients [17] . Another clinical trial showed that the experimental treatment decreased blood pressure from 146.48/97.77 to 129.89/85.96 mmHg, reaching an absolute reduction of 17.14/11.97 mmHg by using HS calyx watery infusions [6] . Notably, this experimental treatment showed a therapeutic effectiveness of 65.12% and a tolerability and safety up to 100%.…”
Section: Anti-hypertensive Efficacy Of Hsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative medicine is practiced in China, Tanzania, Kenya, South Africa, Pakistan, France, Iran, India, USA, Turkey, Rumania, Mexico, and several other countries (de Boer et al , ; Zaidi and Crow, ; Herrera‐Arellano et al , ; Hancianu et al , ; Ndhlala et al , ; Altuner et al , ; Farahnejad et al , ; Liu et al , ; Zheng et al , ; Kitonde et al , ; Vediyappan et al , ).…”
Section: Questionmentioning
confidence: 99%